2003
DOI: 10.1111/1475-6773.00126
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of the Health Care Safety Net, 1996–2001

Abstract: Despite pessimistic predictions and some notable exceptions, the health care safety net grew stronger over the past six years. Given considerable community variation, however, this analysis indicates that policymakers can apply a number of lessons from strong and improving safety nets to strengthen those that are weaker, particularly as the current economy poses new challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 6 publications
0
44
0
1
Order By: Relevance
“…Regarding our concern about research questions at the organizational/ community level, while some safety net institutions survived and even flourished under MMC, others encountered major crises (Sparer et al 2002;Bindman, Yoon, and Grumbach 2003;Felland et al 2003;Jacobson et al 2005;Zuvekas 2005). Some but not all states included rural areas in MMC (Slifkin et al 1998).…”
Section: Background On MMCmentioning
confidence: 99%
“…Regarding our concern about research questions at the organizational/ community level, while some safety net institutions survived and even flourished under MMC, others encountered major crises (Sparer et al 2002;Bindman, Yoon, and Grumbach 2003;Felland et al 2003;Jacobson et al 2005;Zuvekas 2005). Some but not all states included rural areas in MMC (Slifkin et al 1998).…”
Section: Background On MMCmentioning
confidence: 99%
“…Many previous studies have used qualitative methods to examine the safety net in a few communities. 11,12 Others have focused on 1 type of safety net provider. In this article, we look quantitatively at several dimensions of the safety net in all large communities in the country.…”
mentioning
confidence: 99%
“…In addition, policies oriented toward enhancing funding for the safety net and increasing the capacity of safety net providers are likely to be important to ensuring access among the urban uninsured. Researchers have reported a relatively stable trend in safety net capacity in the late 1990s through 2001 (Felland et al 2003), but the absolute level of capacity has been shown to vary widely across communities (Marquis et al 2004), and some research suggests that those disparities may be widening over time (Hoadley, Felland, and Staiti 2004). Increasing budgetary pressures at the federal level and in many states are likely to pose an increasing threat to safety net funding.…”
Section: Discussionmentioning
confidence: 99%